Optimalisasi Kinerja Mesin 2 SINI JBZ 30 Pembuatan Papercup dengan Metode Overall Equipment Effectiveness (OEE) - Prasmoro, Alloysius Vendh; Fauzi, Ahmad (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
Optimizing Machine Performance 2 Here JBZ 30 Making Paper Cup Using Overall Equipment Effectiveness (OEE) Method Case Study at PT. PAS . PT. PAS is a company engaged in manufacturing, to increase the overall power of the engine, in its implementation it is still not optimal in terms of not achieving production targets. This study aims to measure the value of machine tools, to find the causes of problems. The research was carried out on the 2 Sini JBZ 30 engine which has the most breakdowns. Start with a measurement of the overall equipment effectiveness (OEE) value, then look for a factor of six major losses and recommend a bone diagram. The results showed that the average value of the overall equipment effectiveness (OEE) on the 2 Sini JBZ 30 machine was 76.98%, while the ideal standard OEE value was 85%.